An Overview of Biomembrane Functions in Plant Responses to High-Temperature Stress - Niu, Yue; Xiang, Yun (Frontiers in Plant Science, 2018)
Biological membranes are highly ordered structures composed of mosaics of lipids and proteins. Elevated temperature can directly and effectively change the properties of membranes, including their fluidity and permeability, either through a holistic effect involving changes in lipid composition or via interactions between lipids and specific membrane proteins. Ultimately, high temperature can alter microdomain remodeling and instantaneously relay ambient cues to downstream signaling pathways. Thus, dynamic membrane regulation not only perceives temperature changes but also participates in intercellular responses and determines cell fate. Moreover, due to the specific distribution of extra- and endomembrane elements, the plasma membrane (PM) and membranous organelles are individually responsible for distinct developmental events during plant adaptation to heat stress. This review describes recent studies focusing on the roles of various components that can alter the physical state of the plasma and thylakoid membranes as well as the crucial signaling pathways initiated through the membrane system, encompassing both endomembranes and membranous organelles in the context of heat stress responses.